2014
DOI: 10.1177/1524838014555034
|View full text |Cite
|
Sign up to set email alerts
|

Victim Satisfaction With the Criminal Justice System and Emotional Recovery

Abstract: The current study systematically and critically reviewed the empirical literature to evaluate the association between satisfaction with the criminal justice system and adult crime victims' emotional recovery. Despite the widely accepted notion that involvement in the criminal justice system may impact recovery from crime victimization--either beneficially or maliciously--a systematic review of empirical studies that addresses this topic has never been conducted. Electronic literature databases (ISI Web of Know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…To date, there have been no reviews that examine whether RJ produces any psychological benefit to victims compared with customary justice procedures. While previous reviews have found victims are typically satisfied with their experiences of RJ (Latimer et al 2005;Strang et al 2013), there has been mixed results regarding the relationship between self-reported victim satisfaction in criminal justice and cognitive or emotional states post-victimisation (Kunst et al 2014). Therefore, although victims may express greater satisfaction with RJ, it cannot be inferred that this leads to more positive psychological outcomes.…”
Section: The Current Researchmentioning
confidence: 94%
“…To date, there have been no reviews that examine whether RJ produces any psychological benefit to victims compared with customary justice procedures. While previous reviews have found victims are typically satisfied with their experiences of RJ (Latimer et al 2005;Strang et al 2013), there has been mixed results regarding the relationship between self-reported victim satisfaction in criminal justice and cognitive or emotional states post-victimisation (Kunst et al 2014). Therefore, although victims may express greater satisfaction with RJ, it cannot be inferred that this leads to more positive psychological outcomes.…”
Section: The Current Researchmentioning
confidence: 94%
“…Second, the criminal justice system must make certain that all criminal justice practitioners (e.g., law enforcement and prosecutors) recognize that the differential treatment of victims based on their criminal history can cause significant harm, potentially compounding the secondary victimization many victims of domestic violence already experience at the hands of the criminal justice system (Kunst et al, ). Criminal justice practitioners, particularly law enforcement officers, must understand that a victim's prior status as “offender” does not negate her (or his) current status as “victim.” Victims of domestic violence who do not meet the standards of an “ideal” victim still deserve fair and equal treatment and support from criminal justice personnel (Erez & King, ; Raeder, ; Riger et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior systematic literature reviews have often searched for studies that used victims´satisfaction with the criminal justice system as an indicator of effectiveness (e.g. Laxminarayan, Bosmans, Porter, & Sosa, 2013;Kunst, Popelier, & Varekamp, 2015;Wedlock & Tapley, 2016), but satisfaction, due to its generic meaning, is not an appropriate outcome measure to assess legal rights´effectiveness (cf. Biffi et al, 2016).…”
Section: Resolving the Knowledge Gapmentioning
confidence: 99%